(untitled) (Research, Society and Development, 2022)
Objective: To verify the detection rates of new leprosy cases in the State of Pará. Methodology: This is a quantitative, retrospective, descriptive-exploratory study. Results and discussion: 11,687 new cases of leprosy were found in the State of Pará, from 2016 to 2020. The correlation between the high density of cases and the distribution of degrees of physical disability may indicate inefficiency of epidemiological surveillance of leprosy, since it was distributed differently in the IR of Pará. Final Considerations: It can be concluded from this study that physical disabilities represent a challenge for the National Leprosy Control Program (PNCH) and at all levels of care in the State of Pará.